If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(8x + 6) = 3 Reorder the terms: 3 + -1(6 + 8x) = 3 3 + (6 * -1 + 8x * -1) = 3 3 + (-6 + -8x) = 3 Combine like terms: 3 + -6 = -3 -3 + -8x = 3 Solving -3 + -8x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -8x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = 3 + 3 -8x = 3 + 3 Combine like terms: 3 + 3 = 6 -8x = 6 Divide each side by '-8'. x = -0.75 Simplifying x = -0.75
| 0x-3=0 | | 0y-3=0 | | 4x-8-3(x-5)=3(x-1) | | y-15=32 | | -11nk^2+5nk-6y=0 | | 2[1-3(x+2)]=-x | | 54-4x=14x+22 | | 2d-17=3d+8 | | 3(y+7)+4=43 | | 142-7x=20x+22 | | q+3q=2q-6 | | x+1=-15 | | -4r+5=-3r+9 | | 3(-8x)+8=80 | | 3z-3(1-z)=z-17 | | -8h-1=-33 | | 9(y-4)-3y=6(y-6) | | 90+4x+x=180 | | 15=-2p+27 | | -6(-x-10)=10(-x-10) | | 8x-9x=73-82 | | 0.50x+0.15(70)=48.5 | | 35+x=18 | | -7(3a+10)=0 | | 4(w+1)=6-2(1-2w) | | y-81=-12 | | -8y+12=-28 | | 61+x=5 | | 9+8x=72+8 | | 3x-2x=-3-2x | | 19=4n+7 | | 5x+3-4x=9 |